CONVENTION REPORT. (The Accounting Review, 1942)
The article focuses on the twenty-sixth annual convention of the American Accounting Association that was held in New York from December 29 to 30, 1941. The first session started on December 29, 1941. The topic for the first session was related to accounting principles underlying corporate financial statements. Some of the papers discussed were — "The Cost Principles," by Walter A. Staub, "The Revenue and Income Principles," by James L. Dobr and "The Capital Principle," by Samuel J. Broad. The second session was held on the same day. Six years ago in this city at the twentieth annual meeting of the American Association of University Instructors in accounting the association was reconstituted as the American Accounting Association. At that time many felt that what was accomplished at that meeting was only a streamlining of name and only a few recognized the change as particularly significant. For some years prior to 1936 a small group of members were attempting to awaken the association to its opportunity to render a real service.